Deqi Is Double-Faced: The Acupuncture Practitioner's and the Subject's Perspective - Yin, Chang Shik (Evid Based Complement Alternat Med, 2015)
Background. While therapeutic acupuncture perception (deqi) has recently been investigated only for the subject's perception, classical acupuncture discussed acupuncture perception for both the practitioner and the subject. The aim of this study was to explore the practitioner's and the subject's acupuncture perception during acupuncture. Methods. Explorative crossover study to quantitatively document acupuncture perception of both the practitioner and the subject. Eighty-one participants acted as a practitioner or a subject. The practitioner's and the subject's acupuncture perceptions were collected using self-report type checklists. Acupuncture needles were inserted to LI4 or ST36, adopting a four-phase method: insertion into shallow, middle, and deep depths, followed by twirling manipulation. Pain, transmission, dullness, and soreness feelings of the subject and thick, tangled, solid, and empty feelings of the practitioner were analyzed for their correlation. Results. The practitioner's and the subject's perception showed a significant correlation. Acupuncture perception varied over four phases of needling, with a tendency to be rated higher when inserted deep. Perception for LI4 was generally higher than those for ST36. Conclusion. The practitioner's acupuncture perception was successfully documented and analyzed in relation to the subject's acupuncture perception and different needling conditions.